P94 Mortality in HIV positive patients in a large inner city teaching hospital. (18th May 2015) - Hamlyn, Eleanor; Simons, Rebecca; Kulasegaram, Ranjababu
Abstract : Background/introduction: With the advent of highly active antiretroviral therapy (HAART) mortality among HIV positive patients has fallen significantly. Mortality review is important to target care and interventions appropriately. Methods: We reviewed mortality data from 2013 to 2014 for patients under the care of the HIV team at an inner city teaching hospital. There were 39 deaths in our cohort of 3400 patients. Results: Our cohort matched demographic data for people living with HIV in the UK in most respects: male to female ratio was approximately 7:3, 56% were Caucasian, 33% Black African. 21% of patients had acquired HIV via intravenous drug use (although only 2% of people living with HIV nationally are drug users). 28% were men who have sex with men. The median age of death was 47. The most common cause of death was malignancy (44%) followed by sepsis and ischaemic heart disease. Those with a CD4 count <200 at diagnosis survived on average 5.7 years before death. Those with a CD4 count >200 at diagnosis survived 9.7 years on average. Discussion/conclusion: In the post-HAART era, the majority of deaths in people with HIV are not HIV related. Nine patients, however, had an AIDS defining malignancy and three had active opportunistic infections. In the era of HAART, screening for chronic disease and malignancy is vital. Our data suggest that intravenous drug use is a significant factor in people dying at a younger age with HIV. There remains a correlation between late diagnosis and increased risk of death.